Groundwater vulnerability map of Sulaymaniyah sub-basin using SINTACS model, Sulaymaniyah Governorate, Kurdistan Region, Iraq - Hamamin, Dara Faeq; Rebar Aziz Qadir,; Ali, Salahalddin Saeed (Sulaimani Journal for Pure and Applied Sciences, 2016)
The present work locates in the Complex and Unstable Platform of Arabian Plate within the Zagros Fold-Thrust Belt (ZFTB). It expands over an area of 523 Km2 in the Sulaymaniyah Governorate. Lower Cretaceous and Holocene formations are the dominant stratigraphic units exposed in the area. The alluvium intergranular, karstic fissured, and complex aquifers are the principal water-bearing beds occur in the field of the question. The present study deals with the evaluation of groundwater vulnerability to pollution using SINTACS model in addition to the assessment of the validity of four scenarios applied in this work “Normal, Relevant, Drainage impacts and Nitrate scenarios” with the spatial distribution of nitrate “NO3” map. Nitrate spatial map was constructed from 96 water samples collected from domestic and agriculture water wells, emergence from karezes and springs in benefit with the Geographic Information System (GIS). Although the SINTACS method gives good outputs in the evaluation of groundwater vulnerability to pollution, it cannot be used for reliable assessment of the groundwater pollution risk. Therefore, it is necessary to calibrate the original scenarios with nitrate distribution to obtain more accurate results.
Keywords: VulnerabilitySINTACSAquifersNitrate pollution,Semiarid